The Influence of Digital Leadership and Innovative Culture on Innovation Performance Mediated by Digital Innovation in PT Employees. Bank Central Asia Tbk in Central Jakarta - Nazila Inayah; Netania Emilisa; Zulfa Nanda Fathia Mayrisya (Journal of Social Science, 2024)
This research aims to analyze the influence of Digital Leadership, Innovative Culture, Digital Innovation, and Innovation Performance on PT employees. Bank Central Asia Tbk in Central Jakarta and the relationship between these variables. This research method uses correlation research with cross-sectional data, involving 8 branch offices of PT. Bank Central Asia Tbk in Central Jakarta. The variables studied include Digital Leadership, Innovative Culture, Digital Innovation, and Innovation Performance. The results of the analysis show that Digital Leadership and Innovative Culture have a positive effect on Digital Innovation, which in turn has a positive effect on Innovation Performance. However, Digital Leadership does not have a significant direct influence on Innovation Performance. These results show the importance of applying Digital Leadership principles and an innovative culture in supporting the effective adoption of digital technology, which ultimately improves the company's innovative performance.